Altered Indices of Fatty Acid Elongases ELOVL6, ELOVL5, and ELOVL2 Activities in Patients with Impaired Fasting Glycemia - Macášek, Jaroslav; Zeman, Miroslav; Žák, Aleš; Staňková, Barbora; Vecka, Marek (Metabolic syndrome and related disorders, 2021)
Background: Dysregulation of fatty acids (FA) seems to participate in the pathogenesis of disorders such as metabolic syndrome (MetS), cardiovascular diseases, or some cancers. Activities of enzymes FA desaturases and elongases [elongation of very long-chain fatty acid (ELOVL)] significantly influence FA profile in different body compartments. Although the impact of activities of desaturases on cardiometabolic diseases was broadly studied, relatively little attention was devoted to the role of elongases. Methods: Case-control study was carried out in 36 patients (18 men/18 women) with impaired fasting glycemia (IFG) without MetS and 36 age and gender-matched healthy controls. FA profiles in plasma phospholipids (PL) were assessed using gas chromatograph-flame ionization detector and indices of desaturase and elongase activities were calculated. Results: In the IFG group, we observed decreased estimated activities of ELOVL2 and ELOVL5, whereas higher estimated activities of elongase ELOVL6 were noted. IFG group was also characterized by altered composition of plasma PL FA, above all by lower percentage of cis-vaccenic acid (cVA; 18:1n-7) and of total polyunsaturated FA n-6, especially linoleic acid, and by higher proportion of stearic acid and gamma-linolenic acid. Concurrently, elevated estimated activities of desaturases delta-9-desaturase (D9D), D6D were found. Conclusions: Lower estimated activities of ELOVL2 and ELOVL5 with lowered proportion of PL cVA could be associated with disturbances of glucose homeostasis development and their corresponding indices could serve as biomarkers of such risk.
Keywords: ženské pohlaví; studie případů a kontrol; Female; krevní glukóza; Case-Control Studies; Fasting; Humans; lidé; Metabolic Syndrome; metabolický syndrom; Fatty Acid Elongases; elongasy mastných kyselin; Male; mužské pohlaví; omezení příjmu potravy; Blood Glucose